The art of making beads of faith with reference to Buddhism, Christianity and Islam : historic evolution and suggestive significance - Tan, Clara Elizabeth (Kulliyyah of Islamic Revealed Knowledge and Social Sciences, International Islamic University Malaysia, 2016)
This research has made a comparative study of the art of making beads of different faiths with particular reference to Buddhism, Christianity and Islam. They have been considered within the elements of their history, origins and evolution, the variations in types of materials used and possible symbolic influences of those choices, the usage of additional pendants, the association with a leading figure within each of the religions, colour, the use within chanting and recitation, and the etymology of the words used to describe them within each of the relevant languages. The demographics of the populations who use the rosaries have also been investigated to determine any possible correlations between rosary usage and the economic status of the countries of abode of the devotees. Each religion did not develop the idea of a rosary independently and then implement it as part of their prayer ritual. The preferences for any given design and the various types of materials used are based upon two main parameters, the traditions of the particular religion, and the societal cultures that often predate those religious traditions. One of the important goals of this research was to determine where these two factors impacted upon the rosary design within each of the chosen religions. This was then used during the comparative analysis to determine where any possible acculturation may have taken place between the different civilizations, or where prior primitive forms of religious practices display commonalities. During this process the research has also brought to light certain differences within the methodologies of how the different faith systems use natural phenomena as a vehicle for the devotees to understand their own particular faith system better.